2009
DOI: 10.4314/ejhd.v23i1.44832
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exclusive breastfeeding practices in Ethiopia

Abstract: Background: Despite the demonstrated benefits of breast milk, the prevalence of breastfeeding, in-particular exclusive breastfeeding (EBF), in many developing countries including Ethiopia is lower than the international recommendation of EBF for the first six months of life Objective: To assess the practice of EBF and explore its determinants in Ethiopia and provide policy makers and NGOs with relevant information for future planning and interventions. Methods: Raw data collected from nine regions and two city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
116
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(185 citation statements)
references
References 19 publications
50
116
14
1
Order By: Relevance
“…This study identified that employment states as significant variable for EBF of women living with HIV/AIDS. Self-employed women practice EBF than that of government employee which had agreement with other finding of the study conducted in Ethiopia [16]. This could be due to the fact that government employee should serve at least eight hours in the office and cannot have the opportunity to stay with their baby and feeds enough duration.…”
Section: Discussionsupporting
confidence: 79%
“…This study identified that employment states as significant variable for EBF of women living with HIV/AIDS. Self-employed women practice EBF than that of government employee which had agreement with other finding of the study conducted in Ethiopia [16]. This could be due to the fact that government employee should serve at least eight hours in the office and cannot have the opportunity to stay with their baby and feeds enough duration.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, Thai grandmothers trying to feed infants water, rice, and fruit can negatively impact on EBF duration. Similar traditional behaviors have also been reported in the Middle East, Southern Africa, East Africa, China and Brazil [113,123,128,131]. In Zimbabwe, water as well as herbal concoctions, are given to children with the belief that they could improve their health [114].…”
Section: Discussionsupporting
confidence: 52%
“…There is a wide range of variation in the practice of exclusive breastfeeding among developing countries, with the rates documented inBrazil (58%), Bangalore (40%), Iran (28%), Lebanon (10.1%), Southern Ethiopia, a Community Based Cross-Sectional Study Nigeria (20%), Bangladesh (34.5%) andJordan (77%) [9]. In Ethiopia context, 52 % of infants were exclusively breastfed for the first six months, while 56.9% were exclusively breastfed for the first four months [14,21,22].…”
Section: Introductionmentioning
confidence: 99%